2007
DOI: 10.18553/jmcp.2007.13.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Total Knee Replacement Delayed With Hylan G-F 20 Use in Patients With Grade IV Osteoarthritis

Abstract: steoarthritis (OA) and other rheumatic conditions are the leading cause of disability in the United States. 1 The prevalence of OA of the knee in various countries can be estimated as 18% of men and women as inferred by a recent meta-analysis.2 OA can also result in significant direct and indirect costs, which are higher with greater disability. 3 Current therapeutic options for OA are approved to treat the pain associated with the disorder. The American College of Rheumatology recommends the initial use of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 36 publications
2
63
1
3
Order By: Relevance
“…It has been reported that HA injections help relieve pain in certain patients with OA of the knee [19] and may also be used as a therapeutic alternative for this condition when knee surgery is delayed [20]. To date, many meta-analyses or systematic reviews of HA viscosupplementation as a therapy for OA of the knee have been published [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that HA injections help relieve pain in certain patients with OA of the knee [19] and may also be used as a therapeutic alternative for this condition when knee surgery is delayed [20]. To date, many meta-analyses or systematic reviews of HA viscosupplementation as a therapy for OA of the knee have been published [21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analyses have concluded that IA-HA treatment for OA should be considered as a longer-term therapy than other treatments, with a clinically relevant effect size equivalent or greater than other analgesics (27,28). Furthermore, treatment with repeated cycles of IA-HA seems to delay surgical interventions in knee and hip osteoarthritis as shown by several studies (29)(30)(31). Despite this evidence, the mechanism(s) by which HA alleviates joint pain remains not clear.…”
Section: Hyaluronic Acid: Injection Therapies Innovationsmentioning
confidence: 99%
“…All VIS formulations are very well tolerated in comparison to NSAID therapy and reactions are typically benign and transient. VIS may also delay total knee arthroplasty (TKA) which may reduce the need for revision surgery especially in younger patients [Waddell and Bricker, 2007;Burns et al 2006]. VIS is an important conservative treatment modality in the care and treatment of patients with OA of the knee and certainly may be helpful in other joints as has been noted outside the United States.…”
Section: Therapeutic Advances In Musculoskeletal Disease 2 (3)mentioning
confidence: 99%